2020
DOI: 10.1016/j.jwpe.2020.101592
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and detoxification of leather tannery effluent by a newly developed bacterial consortium GS-TE1310 for environmental safety

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…As the COD and BOD are considered important parameters to evaluate the degree of pollution, their decrease represents biodegradation. In this study, it was found that the untreated effluent containing high COD and TDS might be due to organic matter and salts, while high BOD suggested low dissolved oxygen due to organic matter, as previously described by Saxena, Purchase, Mulla, and Bharagava [ 10 ] and Saxena et al (2020). In this study, the COD decreased by >75%, while the BOD decreased by >90% after decolorization, which suggested biodegradation.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As the COD and BOD are considered important parameters to evaluate the degree of pollution, their decrease represents biodegradation. In this study, it was found that the untreated effluent containing high COD and TDS might be due to organic matter and salts, while high BOD suggested low dissolved oxygen due to organic matter, as previously described by Saxena, Purchase, Mulla, and Bharagava [ 10 ] and Saxena et al (2020). In this study, the COD decreased by >75%, while the BOD decreased by >90% after decolorization, which suggested biodegradation.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, in the current study, upon increasing yeast extract concentrations to 1%, the decolorization increased within 2 h, in agreement with previous studies [ 2 , 28 ]. No visible decolorization was detected among single isolates from mixed cultures ( Figure S2 ), as mixed cultures are known to be superior due to consumption of the produced toxic metabolites by other microorganisms present in the mixed culture [ 10 , 16 , 41 ]. In the current study, the extent of decolorization of the screened mixed cultures was performed in MSM-Y along with sterile and non-sterile real wastewater to test decolorization under real conditions in the industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid urbanization and industrialization have resulted in the discharge of enormous amounts of waste pollutants (including emerging contaminants) into the environment, which yields more pollution in its turn. [1][2][3][4][5][6][7][8][9][10] The majority of colored effluents consisting of dyes released to the environment from the textile dyestuff and dyeing industries are escalating problems. 11,12 Azo dyes are the most common colorants used in the textile industry and account more than 50% of the weight used for coloring purposes.…”
Section: Introductionmentioning
confidence: 99%